MEMPERKUAT KETERAMPILAN ANALISIS SISWA: PENDEKATAN PEMBELAJARAN KONSTRUKSI BANGUNAN CASE BASED LEARNING DI SMK - Mawar Helena Manuella Napitupulu (CV. ADIBA AISHA AMIRA, 2024)
This study aims to examine the effectiveness of applying case-based learning (CBL) with a construction building theme to strengthen the analytical skills of vocational high school (SMK) students. This study uses a quasi-experimental method with a one-group pretest-posttest design. The research sample is 30 SMK students in grade X who were selected randomly. The research instruments used are analytical tests and observation sheets. The results of the study show that there is a significant increase in students' analytical skills after participating in CBL learning. This increase is seen in the aspects of problem identification, data analysis, and decision making. This shows that CBL with a construction building theme is an effective learning approach to strengthen the analytical skills of SMK students.